Surgical treatment of rheumatoid forefoot: evaluation of functional outcome and quality of life - Macedo, Rodrigo Sousa; Pires, Eduardo Araujo; Sposeto, Rafael Barban; Sakaki, Marcos Hideyo; Santos, Alexandre Leme Godoy dos; Fernandes, Túlio Diniz (Scientific Journal of the Foot & Ankle, 2018)
Objective: To evaluate the functional outcome and quality of life of patients with rheumatoid arthritis (RA) who underwent resection arthroplasty of the first to fifth metatarsal heads. Methods: Prospective case series study in which 8 feet of 5 patients underwent resection arthroplasty of the five metatarsal heads via a plantar approach to the lateral rays and via a medial approach to the first metatarsal. Dressing and orthotics were used for 3 months to correct the position of the toes. Patients were evaluated in the preoperative period and at least one year after the procedure using two functional evaluation scales (AOFAS lesser toes and AOFAS hallux) and one quality of life scale (EQ-5D). All results were subjected to statistical validation using the Mann-Whitney U test. Results: The subjects had a mean age of 71 years, with a prevalence of the female gender. The mean AOFAS lesser toe and AOFAS hallux scores increased from 38.6 and 24.5 preoperatively to 85.7 and 83.1 postoperatively, respectively (p<0.001). The quality of life scores measured through the EQ-5D improved from 8.0 to 5.6, on average. Conclusion: Resection arthroplasty of the five metatarsal heads improves the function and quality of life in the short term of patients with rheumatoid foot. Level of Evidence IV; Therapeutic Studies; Case Series.